2003
DOI: 10.1002/yea.1058
|View full text |Cite
|
Sign up to set email alerts
|

Alanine : glyoxylate aminotransferase of Saccharomyces cerevisiae–encoding gene AGX1 and metabolic significance

Abstract: Alanine : glyoxylate aminotransferase is one of three different enzymes used for glycine synthesis in Saccharomyces cerevisiae. The open reading frame YFL030w (named AGX1 in the following), encoding this enzyme, was identified by comparing enzyme specific activities in knockout strains. While 100% activity was detectable in the parental strain, 2% was found in a YFL030w::kanMX4 strain. The ORF found at that locus was suspected to encode alanine : glyoxylate aminotransferase because its predicted amino acid seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 43 publications
0
26
0
Order By: Relevance
“…Although AGX1 is not essential for viability, yeast lacking AGX1 in a shm1, shm2, and gly1 background are unable to grow on medium that contains ethanol unless exogenous glycine is provided (16). Plasmid-expressed yeast Agx1 protein can restore ethanol-dependent growth to an agx1-deficient strain, YCG-F r (16). The Agx1 enzyme has 23% identity to human AGT, with residues that are conserved among all AGTs, such as a common pyridoxal 5Ј-phosphate-binding site (Fig.…”
Section: Expression Of Agt Disease Variants In Yeast-yeast Alaninementioning
confidence: 99%
See 2 more Smart Citations
“…Although AGX1 is not essential for viability, yeast lacking AGX1 in a shm1, shm2, and gly1 background are unable to grow on medium that contains ethanol unless exogenous glycine is provided (16). Plasmid-expressed yeast Agx1 protein can restore ethanol-dependent growth to an agx1-deficient strain, YCG-F r (16). The Agx1 enzyme has 23% identity to human AGT, with residues that are conserved among all AGTs, such as a common pyridoxal 5Ј-phosphate-binding site (Fig.…”
Section: Expression Of Agt Disease Variants In Yeast-yeast Alaninementioning
confidence: 99%
“…We examined whether expression of plasmid-derived human AGT could complement growth of yeast lacking AGX1 in the YCG-F r strain (16). This strain is unable to grow on glycine-free medium, because it cannot synthesize glycine endogenously (16).…”
Section: Expression Of Agt Disease Variants In Yeast-yeast Alaninementioning
confidence: 99%
See 1 more Smart Citation
“…In yeast, disruption of AGT can lead to glycine auxo-trophy. For example, a yeast AGT deletion strain was unable to grow when glucose was the only carbon source, unless glycine was supplemented (Schlosser et al, 2004). The importance of hepatic AGT in minimizing endogenous oxalate production in some mammals is clearly shown by the autosomal recessive disorder of glyoxylate metabolism known as primary hyperoxaluria type 1.…”
Section: Primary Function Of Agtmentioning
confidence: 99%
“…aegypti AGT showed that this AGT, unlike mammalian AGTs, functions virtually exclusively on the glyoxylate to glycine pathway (i.e., functions as a true AGT) (Han et al, 2006). It has been shown that AGT is essential in human and yeast (Danpure et al, 1996;Danpure, 2001;Schlosser et al, 2004) and it likely is crucial in insects. In our previous study, we demonstrated that Ae.…”
Section: Possible Driving Force For Mosquito Agt Functional Adaptatiomentioning
confidence: 99%